Chatting about your world - Urgilés Borja, Fresia Eulalia (2013)
The purpose of the following dissertation is to demonstrate that adolescent students achieve meaningful learning and reinforcement of English oral skills when the didactic material used is based on their needs and social interests. Active oral participation can occur in a more relaxed and natural way when teachers present activities which focus on intrinsic motivation. Therefore, Chatting About Your World” was created and designed as an innovative didactic material to foster the active and creative oral participation of English oral skills._x000D_ A case study was developed to monitor the implementation of Chatting About Your World”. The participants for the research were adolescent girls from eleven to fifteen years old. The results of this case study showed that students developed a positive attitude towards practicing English oral skills with the new didactic material. Chatting About Your World” includes activities students found interesting and motivating to work with. The researcher could observe an improvement on their English individual oral performance as well as on the students’ creative and cooperative development.